Spotting plants' microfilament morphologies and nanostructures - Almeida, Ana (2019)
The tracheary system of plant leaves is composed of a cellulose skeleton with diverse hierarchical structures. It is built of polygonally bent helical microfilaments of cellulose-based nanostructures coated by different layers, which provide them high compression resistance, elasticity, and roughness. Their function includes the transport of water and nutrients from the roots to the leaves. Unveiling details about local interactions of tracheary elements with surrounding material, which varies between plants due to adaptation to different environments, is crucial for understanding ascending fluid transport and for tracheary mechanical strength relevant to potential applications. Here we show that plant tracheary microfilaments, collected from Agapanthus africanus and Ornithogalum thyrsoides leaves, have different surface morphologies, revealed by nematic liquid crystal droplets. This results in diverse interactions among microfilaments and with the environment; the differences translate to diverse mechanical properties of entangled microfilaments and their potential applications. The presented study also introduces routes for accurate characterization of plants' microfilaments.